2013
DOI: 10.1016/j.jmaa.2012.08.004
|View full text |Cite
|
Sign up to set email alerts
|

On a sequence of sparse binomial-type polynomials

Abstract: a b s t r a c tThe sequence of sparse polynomials  n k=0  n k  z k(k−1)/2 arises naturally in a graph theoretic setting. Here we study these polynomials in their own right; we derive some identities and study both algebraic and analytic properties, among them the distribution of real and complex zeros.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 4 publications
2
9
0
Order By: Relevance
“…Moreover, those polynomials may also be considered to be interesting because of their close connection with the Jacobi Theta functions investigated in [4]. In the paper [2] the authors prove algebraic and analyic properties, and in addition to those, in [1] they obtain upper and lower bounds for the values of these polynomials for 0 < z < 1. Furthermore, in [1] the asymptotic relation log f n 1 y ∼ 1 2 log y log 2 n, n → ∞, (1.2) has been established.…”
Section: Introductionmentioning
confidence: 96%
“…Moreover, those polynomials may also be considered to be interesting because of their close connection with the Jacobi Theta functions investigated in [4]. In the paper [2] the authors prove algebraic and analyic properties, and in addition to those, in [1] they obtain upper and lower bounds for the values of these polynomials for 0 < z < 1. Furthermore, in [1] the asymptotic relation log f n 1 y ∼ 1 2 log y log 2 n, n → ∞, (1.2) has been established.…”
Section: Introductionmentioning
confidence: 96%
“…In [3] it was shown that for any integer k ≥ 1, the polynomial f 2,2k+1 (z) is divisible by z k + 1. This gives rise to the question whether there are similar divisibility results for polynomials f m,n (z) with other parameters m. Computations indicate that this is indeed the case when m is a power of 2, with certain additional restrictions.…”
Section: Divisibility Propertiesmentioning
confidence: 99%
“…Proof of Proposition 3.1. We use the basic idea of the proof of Proposition 2.1 in [3], which is actually our case µ = 1. Using the definition (1.2), we have…”
Section: Divisibility Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In [3] it was shown that the roots of each polynomial f n (z), as defined by (1.1), all lie in the annulus…”
Section: Bounds On the Roots Ofmentioning
confidence: 99%